A new approach to detect a set of SNP‐SNP markers: Combining ARMS‐PCR with SNaPshot technology. Issue 13 (11th May 2020) - Zhang, Ranran; Tan, Yu; Jian, Hui; Qu, Shengqiu; Liu, Yuqing; Zhu, Jing; Wang, Li; Lv, Meili; Liao, Miao; Zhang, Lin; Yang, Fan; Liang, Weibo
Abstract: Microhaplotypes are a new promising type of forensic genetic marker. Without the interference of stutter and high mutation rates as for STRs, and with short amplification lengths and a higher degree of polymorphism than single SNP, microhaplotypes composed of two SNPs, SNP–SNP, have a strong application potential. Currently, the most common method to detect microhaplotypes is massive parallel sequencing. However, the cost and extensive use of instruments limit its wide application in forensic laboratories. In this study, we screened 23 new SNP–SNP loci and established a new detection method by combining a multiplex amplification refractory mutation system‐based PCR (ARMS‐PCR) and SNaPshot technology based on CE. First, we introduced an additional deliberate mismatch at the antepenultimate base from the 3′ end of primers when designing ARMS‐PCR for SNP 1 (the first SNP of the SNP–SNP). Then, single base extension primers for SNaPshot assay were designed next to the position of SNP 2 (the second SNP). Finally, 15 loci were successfully built into four panels and these loci showed a relatively high level of polymorphism in the Southwest Chinese Han population. All the loci had an average probability of informative genotypes ( I value) of 0.319 and a combined discrimination power of 0.999999999. Therefore, this new detection system will provide a valuable supplement to current methods.